Tokugawa Confucian Sermons as Popular Emotional Education: The Moral and Pedagogical Philosophy of Hosoi Heishū - Takao, Makoto Harris ca. 20./21. Jh. (Journal of religious history, 2021)
This article contributes to the growing literature on the nexus of religion and emotion, thinking through the ways in which historians of Japan can make interventions in the field, and exploring research methodologies that speak to a pre-modern and non-Christian milieu. In looking to the moral and pedagogical philosophy of Hosoi Heishū (1728-1801), a Tokugawa Confucian teacher and itinerant preacher, this article places an emphasis on the use of contextualised and historically-specific emic categories of belief and feeling. To do so, it explores the popularising movement of Japanese Confucianism in the late eighteenth century, tracing Hosoi's development of vernacular sermonising and his identification of emotion as both a subject and object of instruction. His rhetorical style and pedagogy is unpacked, followed by an analysis of his popular reception, before turning to a sermon case study to observe these ideas in action. This article offers new insights into the viewing habits and emotional expectations of Tokugawa audiences, underscoring the ways in which emotion terms and concepts can change meaning in how they are defined, embodied, expressed, and valued as part of a broader habitus.